Effect of Replacing Rice Polish with Mulberry (Morus alba) Leaf Powder in Diet Containing Phytase Enzyme on Performance and Haemato-biochemical Parameters of Commercial Laying Hens - Siddiqui, Rukkiya; Mondal, Bidhan C.; Kumar, Ripusudan; Kaur, Manveen; Kumar, Ashoka; Palod, Jyoti; Lata, Manju (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was carried out to discern the effect of replacing rice polish with mulberry (Morus alba) leaf powder in a diet containing phytase enzyme on growth performance, nutrient utilization, egg quality, and haemato-biochemical parameters of commercial laying hens. Seventy-two 28-week-old White Leghorn laying hens were subjected to 12 weeks feeding experiment. Hens were randomly distributed into four treatment groups with 18 birds per treatment. Hens of T1 (control) group were fed with basal diet, whereas in T2, T3, and T4 groups, rice polish was replaced with mulberry leaf powder at 1/3rd, 2/3rd, and complete levels, respectively. A fixed level of phytase enzyme at 250 FTU was included in all four treatment groups. The results indicated that the overall cumulative performance of the laying hens in terms of feed intake, egg production, and FCR was not affected significantly. Dry matter utilization and yolk color were significantly (p <0.05) increased in T4 group compared to T1 group. The egg quality parameters in terms of egg weight, shape index, shell weight (gm or %), shell thickness, albumen quality, and Haugh unit also did not differ significantly; however, the serum and egg yolk cholesterol was significantly (p <0.05) reduced in T3 and T4 group, while the yolk triglyceride of the treatment groups T2, T3 and T4, and serum triglyceride of T3 group were significantly (p <0.05) lower as compared to control T1 group. The haemato-biochemical parameters also showed no significant differences among the treatment groups, except serum glucose content significantly reduced in the T4 group. In general, adding mulberry leaf powder to the diet of laying hens in place of rice polish did not affect performance, nutrient consumption, egg quality, or biochemical markers, whereas it reduced yolk cholesterol and triglyceride levels, as well as improved yolk color. Hence rice polish (upto the level of 4.5% in diet) could be completely replaced with mulberry leaf powder in laying chicken feed without imposing any negative impact on performance.